Epidemiological and Clinical Study of Phenylketonuria (PKU) Disease in the National Screening Program of Neonates, Fars Province, Southern Iran - S Senemar; H Ganjekarimi; M Fathzadeh; S Senemar; B Tarami; M Bazrgar (Tehran University of Medical Sciences, 2009)
"nBackground: Classic phenylketonuria (PKU) is a rare metabolic disorder that results from a deficiency of a liver enzyme known as phenylalanine hydroxylase (PAH). In this study, we researched about PKU epidemiological factors and health quality of patients after the neonatal screening program."nMethods: Neonatal screening for PKU was conducted by one neonatal screening center in Fars Province, in Shiraz Paramedical University. All Fars infants must refer only to this center, in which a heel prick blood sample  of each infant was collected at 72 hours postnatal on to standard filter paper and asked questions from the children's parent's and the doctor examined the patients receiving phenylalanine- free milk through examining the children's development. PKU was screened by Fluorometric method."nResults: Totally of 70477 newborns screened for PKU, 15- cases of PKU detected with an incidence of 1:4698. In "Eghlid", that is a city in Fars Province. The prevalence of the disease is 1:382 of newly born babies. The frequency of familial marriage in these children's parents is 86.6%. Twenty nine percent of them were observed among those who had married their close relatives. Mean rate of normal development in PKU patients was 95%."nConclusion: Consanguineous marriage is a major cause in that pattern particular in Iranian. The treatment of PKU after newborn screening is used. With special diet in above of 90% newborn is satisfactory. Now screening should be executed for all of family that they have familial history of PKU in Iran.